2006
DOI: 10.1021/jp064332n
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structure−Activity (Affinity) Relationship (QSAR) Study on Protonation and Cationization of α-Amino Acids

Abstract: A quantitative structure-activity (affinity) relationship (QSAR) study is carried out to model the proton, sodium, copper, and silver cation affinities of alpha-amino acids (AA). Stepping multiple linear regression (MLR), partial least squares (PLS), and artificial neural network (ANN) approaches are applied to elucidate the multiple factors affecting these affinities. The MLR and PLS models reveal that the variation in proton affinity is attributed to the highest electrophilic superdelocalizability of nitroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…This result was intriguing because the shape of the molecules itself was relevant rather than electronic properties. It has been reported that cation affinities of amino acids were associated with degree of linearity [18], which is a direct index of the flexibility of molecule [19]. It was thus suggested that the shape properties of target compounds affect their interaction with other molecules to promote or inhibit their ionization.…”
Section: Resultsmentioning
confidence: 99%
“…This result was intriguing because the shape of the molecules itself was relevant rather than electronic properties. It has been reported that cation affinities of amino acids were associated with degree of linearity [18], which is a direct index of the flexibility of molecule [19]. It was thus suggested that the shape properties of target compounds affect their interaction with other molecules to promote or inhibit their ionization.…”
Section: Resultsmentioning
confidence: 99%
“…ANN In order to build reliable and predictive QSAR models, we adopted the ANN technique, which has been proven to have outstanding non-linear approximation ability [22,23,37] . A typical ANN consists of an input layer, a hidden layer, and an output layer.…”
Section: Methodsmentioning
confidence: 99%
“…The large amount of variables in E-state indices can fully represent the structure characters of molecules, such as information about non-covalent interactions, which may be important to the occurrence of anti-MDR activity. The artificial neural network (ANN), used as a modeling technique, has recently become a popular and powerful chemometric tool [21][22][23] . Compared with classical statistical methods, ANN-based approaches do not require preliminary knowledge of the mathematical form of the relationship between the variables [24] , which makes the ANN suitable for extrapolating the complex and unsure relationships between the biological phenomenon and the structure of the compounds.…”
Section: Introductionmentioning
confidence: 99%
“…For the calculation of the quantum chemical molecular descriptor used in QSAR studies, semi empirical methods such as AM1 and PM3 mainly have been used (Saeed and Elias, 2010;Saeed et al, 2010a;2010b). However, DFT method has been used recently for the prediction of physiochemical and biological properties of organic molecules (Shaik et al, 2010;Siu and Che, 2006).…”
Section: Introductionmentioning
confidence: 99%